QRS Complex Detection On Heart Rate Variability Reading Using Discrete Wavelet Transform - Arga Wihantara; I Dewa Gede Hariwisana; Andjar Pudji; Sari Luthfiyah; Vijay Anant Athavale (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Heart Rate Variability or heart rate in humans is used to monitor the heart rate in humans, the function of the heart rate monitor is to monitor the human heart rate. The purpose of making this tool is to compare the results of heart rate readings using the discrete wavelet transform method to facilitate the detection of R peak. This can be learned by evaluating and studying each decomposition result from level 1 to level 4 on Discrete Wavelet Transform processing using Haar mother wavelets. This study uses a raspberry pi 3B as a microcontroller as a data processor that is obtained from the ECG module. From this study, it can be concluded that in heart rate readings, level 2 decomposition details coefficient has the best value as data processing that helps for heart rate readings with an error value of 0.531%, HRV readings of 0.005 in comparison with phantom tools and a standard deviation of 0.039. The advantage of this tool is a good precision value in HRV and BPM readings. In reading the HRV of the respondent, it was found that each initial condition of the patient's HRV would be high due to the respondent's unstable condition. The disadvantage of this tool is that there is a delay in running the program, there is no display in the form of a signal in real time.